BIOKONVERSI SERAT KELAPA SAWIT MENJADI GLUKOSA DENGAN DILUTED-ACID HYDROTHERMAL TREATMENT - Nata, Iryanti Fatyasari; Norlina, Norlina; Pangesti, Mira (Semarang State University, 2016)
Fiber cake (FC) is a one of effluent of Crude Palm Oil (CPO) industry. This effluent can be decreased by using FC for bioethanol production. FC is actually Palm Kernel Press Cake (PKC) a residue of palm oil extraction, which containing 57.9% cellulose and 18% klason lignin, and containing 14.94% hemicellulose. This study aimed to determined the effect of fiber concentrations and reaction time forÂ glucose production to investigate the structure of morphology and crystalinity of the fiber cake before and after hydrothermal treatment. Fiber cake was treated by hydrothermal reactor using catalysts 2% H2SO4 (v/v) and 150 oC for 2 hour. Variations concentration of fiber cake which is 2.5%; 5%; 7.5%; and 10% w/v and time variations for 1, 2, 3, 4 hours. The highest glucose concentration was found at Â 2.5% FC for 3 hour about 2.336 Â± 0.015 mg/mL. Scanning electron microscope (SEM analysis results and X-Ray Diffraction (XRD) is known the smooth surface structure to be broken an rough after the hydrolysis process and also improvement of the crystal structure of fiber cake from 27.57% to 31.15%.